Effect of Nonionic Surfactants on the Crystallinity and Thermal Stability of Poly(vinyl alcohol) Film - Diana M. da Costa; Vanessa R. R. Cunha; Gustavo F. Perotti; Ruan R. Henriques; Jorge Amim Jr.; Ana L. Shiguihara (Orbital: The Electronic Journal of Chemistry, 2020)
In this study, poly(vinyl alcohol) (PVA)/surfactant films were prepared by casting technique. Two nonionic surfactants with different alkyl chain lenghts (Tween 20 and Tween 40) were used. PVA/Tween 20 and PVA/Tween 40 films were characterized by means of Fourier Transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and thermogravimetric analysis (TGA). FTIR spectra of PVA/Tween films indicated the presence of hydrogen bond interactions between the Tween surfactants and PVA. XRD results showed that the incorporation of Tween 20 and 40 into the PVA film decreased the crystallinity of PVA.TGA curves revealed an increase in the thermal stability of PVA film in the presence of the surfactants.DOI: http://dx.doi.org/10.17807/orbital.v12i4.1514